Molecular Encapsulation of Lavender Essential Oil by b-Cyclodextrin and Dimethyl Dihydroxy Ethylene Urea for Fragrance Finishing of Cotton Fabrics - Khajavi, R.; Ahrari, M.; Toliyat, T.; Bahadori, L. (Asian Journal of Chemistry, 2012)
Volatility of fragrance compounds on aroma textiles is considered as a deficiency by producers and consumers. Molecular encapsulation can be used for preserving the fragrance compound as the guest molecule so prolonging the fragrance of the textiles. In this study molecular encapsulation by b-cyclodextrin (b-CD) applied for hosting of lavender essential oil (LEO) on cotton fabric. Dimethyl dihydroxy ethylene urea also used for bounding the b-cyclodextrin to cotton fabric. Phenolphthalein and spectrophotometric methods used for the detection and measurement of b-cyclodextrin, lavender and the durability of fragrance finishing on cotton fabric samples. Lavender essential oil bonded to b-cyclodextrin according to their mutual hydrophobic character and treated samples with molecular encapsulated fragrance compound showed more durability in comparison with untreated and dimethyl dihydroxy ethylene urea treated samples.